Trampoline inspired stretchable triboelectric nanogenerators as tactile sensors for epidermal electronics. (March 2021) - He, Jiahui; Xie, Zhaoqian; Yao, Kuanming; Li, Dengfeng; Liu, Yiming; Gao, Zhan; Lu, Wei; Chang, Lingqian; Yu, Xinge
Abstract: Recent advances in flexible electronics have brought great promotions to the next generation of wearable devices, like electronic skin (E-skin). Nevertheless, the powering issue still limits the size, weight and cost for E-skin. Here, trampoline inspired mechanics design and processing techniques in epidermal electronics are combined together to develop a thin, soft, stretchable self-powered tactile sensors based on triboelectric effect for E-skin. With the assistance of microstructure modifying by sandpapers, the TENG sensor exhibits great improved electrical performance and capable of distinguishing a broad range of pressure, with a great sensitivity of 0.367 mV Pa −1 . The resulted TENG sensor exhibits excellent stretchability and sensing stability with accurate unchanged signal outputs even under a high-level strain up to 35%. Demonstrations of the sensors associating with the integration with a glove for human-machine interfaces and the development of a 4 × 4 tactile array for pressure mapping and recognition of contact objects, offers great opportunity for next generation self-powered E-skin. Graphical Abstract: ga1 Highlights: ● Trampoline inspired design in electrode of the TENG sensor for great stretchability. ● TENG-based tactile sensors exhibit great and stable electrical performance under high-level strain. ● E-skin format TENG sensor array for tactile mapping.